Advances in phase-stepping real-time holography using photorefractive sillenite crystals - Gesualdi, M. R. R.; Barbosa, E. A.; Muramatsu, M. (Natl Inst Optoelectronics, 2006)
This work presents a review of recent developments in phase-stepping real-time holographic interferometry with photorefractive sillenite crystals. Quantitative results are shown in micro-rotation, micro-displacement, and micro-deformation measurements, and in wave-optics and surface analysis as well. The phase stepping was carried out in a four-frame process and the resulting phase map was unwrapped by applying a sin/cos filter. The experimental results are in good agreement with the ones obtained through other means, showing the promising potentialities of phase-stepping real-time holographic interferometry for in situ visualisation, monitoring and analysis in non-destructive testing.
Keywords: holography; interferometry; phase shifting